Essential oil content of cardamom (Elettaria cardamomum Maton) by Hand-held Electronic Nose - Ghosh, N Bhattacharya, N K Leela*, A M Muneeb, S Mukherjee, D (Journal of Spices and Aromatic Crops, 2017)
Cardamom (Elettaria cardamomum Maton.) is one of the most expensive spices in the world. Essential oil is the most functionally important component of cardamom and is described as sweet, spicy, warm, camphoraceous and citrusy. The quality of cardamom is assessed by the essential oil content and its composition. Design of hand-held E-nose and evaluation of quality of cardamom in terms of its essential oil content is reported here.